The Effect of STAD (Student Teams Achievement Division) Model On Student Participation of Class III Elementary School - Fayza Lintang Pramudya; Anni Malihatul Hawa (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
This study aims to understand how the STAD model, assisted by Sangtar props, affects the learning activeness of third-grade students in elementary school. A quasi-experimental design with non-equivalent control groups was used. The participants were third-grade students from SDN Jatijajar 01 (experimental group) and SDN Jatijajar 02 (control group). Data were collected through questionnaires, observation sheets, unstructured interviews, and documentation. Data analysis involved Simple Linear Regression and Independent Sample T-Test. The findings indicate that the STAD model significantly enhances student learning activities, as evidenced by a sig value of 0.002 in the Independent Sample T-Test. However, a negative effect was observed in the Simple Linear Regression Test, with a sig value of 0.000.